Metacognitive Therapy for Alcohol Use Disorder: A Systematic Case Series - Caselli, Gabriele; Martino, Francesca; Spada, Marcantonio M.; Wells, Adrian (Frontiers in Psychology, 2018)
Alcohol Use Disorder (AUD) is a debilitating condition with serious adverse effects on health and psycho-social functioning. The most effective psychological treatments for AUD show moderate efficacy and return to dysregulated alcohol use after treatment is still common. The aim of the present study was to evaluate Metacognitive Therapy (MCT) as applied to AUD. Five patients were treated using a non-concurrent multiple baseline design with follow-up at 3- and 6-months time points. Each patient received 12 one-hour sessions of MCT. Following MCT all patients demonstrated large and clinically meaningful reductions in weekly alcohol use and number of binge drinking episodes that were upheld at follow-up in almost all cases. Metacognitive beliefs, as secondary outcome, also changed substantially. The findings from this study offer preliminary evidence of positive effects associated with MCT in AUD and support the need for a definitive trial of MCT in addictive behaviors.